Model For Improving The Performance Of Hospital Management Information System Services Through Transformational Leadership - Kosidin Kosidin; Munir Munir; Puspo Dewi Dirgantari; Asep Wahyudin (Green Publisher Indonesia, 2024)
The role of Transformational Leadership in hospital organizations is very important, where hospitals are organizations that have a complex environment, there is a lot of unclear information. With the increase in health services to the community along with changes in demographics, changes in health service technology, and the adoption of new information technology. So performance measurement is important in order to improve the quality of health services. The aim of this research is to find out how transformational leadership influences the success of hospitals management information systems (HMIS). The method used was a quantitative descriptive and verification survey with 181 respondents from 15 hospital in the city of Bandung. The sampling technique uses proportionate stratified random sampling. Data analysis using structural equation modeling (SEM) with partial least squares (PLS). The findings of the proposed hypothesis are that the quality of technology, transformational leadership, and users have a significant effect on service performance. Users can mediate technology quality, transformational leadership and service performance. Conclusion of the study is the novelty of the development of the information system success model by adding the context of transformational leadership in evaluating the success of the information system, where transformational leadership has a positive effect on improving the performance of hospital management information system services through users. Implications of the results of this study contribute to the development of an information system success model that can be used to evaluate the success of information systems in general.